1997
DOI: 10.1042/bj3240597
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic equilibrium between calcineurin and kinase activities regulates the phosphorylation state and localization of the nuclear factor of activated T-cells

Abstract: The nuclear factor of activated T-cells (NFAT p ) is a phosphorylated transcription factor that resides in the cytoplasm of unactivated T-cells. T-cell activation results in the activation of the phosphatase calcineurin (CaN), which leads to the dephosphorylation and subsequent nuclear localization of NFAT p . We have investigated the role of kinases in the phosphorylation state and subcellular localization of NFAT p . The phosphorylation state and nuclear\cytoplasmic location of NFAT p were determined in unst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…The phosphorylated form of NFAT1 appears to have a molecular mass of approximately 135 kDa, whereas the active, dephosphorylated form, which is sequestered in the nucleus, is about 120 kDa (23,52,55). In line with our previous results we found that treatment with PP1 alone caused a slight activation of NFAT1 in both types of cells, an effect that was more pronounced in the Wnt-5a high cells (Fig.…”
Section: Wnt-5a-induced Activation Of Yes and Cdc42 Counteracts Its Casupporting
confidence: 81%
“…The phosphorylated form of NFAT1 appears to have a molecular mass of approximately 135 kDa, whereas the active, dephosphorylated form, which is sequestered in the nucleus, is about 120 kDa (23,52,55). In line with our previous results we found that treatment with PP1 alone caused a slight activation of NFAT1 in both types of cells, an effect that was more pronounced in the Wnt-5a high cells (Fig.…”
Section: Wnt-5a-induced Activation Of Yes and Cdc42 Counteracts Its Casupporting
confidence: 81%
“…Highly phosphorylated NFAT normally resides in the cytosol. However, TRPC6-mediated activation of calcineurin results in dephosphorylation of NFAT, causing some of it to translocate to the nucleus where it can regulate gene expression (Scott et al, 1997;Kuwahara et al, 2006). Using an assay based on cell fractionation, we observed that 100 M NMDA treatment for 24 h caused a marked increase in the amount of NFAT that is located in nuclei (a cell fraction enriched in histone) but did not produce a substantial effect on cytosolic NFAT (a much larger pool in a cell fraction in which actin is abundant) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…thereby allows its translocation to the nucleus (Scott et al, 1997). A contribution of TRPC6 channels to this pathway was initially established in cardiac cells, where it is thought to play a role in angiotensin-mediated cardiac hypertrophy (Kuwahara et al, 2006).…”
Section: Downloaded Frommentioning
confidence: 99%
“…Thereby, the impact of Ca 2+ on gene expression exceeded its role in the nuclear envelope, where Ca 2+ is essential for modulating immediate early genes by modulating the DNA-binding of transcription factors (e. g. cAMP-responsive element binding protein CREB [191,192,198,199,200]). Ca 2+ triggers the activation of transcription factors such as the nuclear factor of activated T cells (NFAT) [201,202,203,204,205,206] and the serum response factor-related proteins (RSRF or the myocyte enhancer factor 2 (MEF2) [207]) by calcineurin [208] or Ca 2+ -sensitive kinases (e. g. Cam-kinase IV [207]). In the case of NFAT, the Ca 2+ /calmodulin-activated protein phosphatase-2B (calcineurin) dephosphorylates NFAT resulting in its translocation into the nucleus [208] to form a heteromeric transcriptional activator complex with activator-protein-1 (AP-1) and initiates gene expression [202].…”
Section: Nomentioning
confidence: 99%
“…Ca 2+ triggers the activation of transcription factors such as the nuclear factor of activated T cells (NFAT) [201,202,203,204,205,206] and the serum response factor-related proteins (RSRF or the myocyte enhancer factor 2 (MEF2) [207]) by calcineurin [208] or Ca 2+ -sensitive kinases (e. g. Cam-kinase IV [207]). In the case of NFAT, the Ca 2+ /calmodulin-activated protein phosphatase-2B (calcineurin) dephosphorylates NFAT resulting in its translocation into the nucleus [208] to form a heteromeric transcriptional activator complex with activator-protein-1 (AP-1) and initiates gene expression [202]. In vascular smooth muscle cells NFAT activation by increasing cytosolic free Ca 2+ concentration depends on the patterns of the Ca 2+ signalling observed in response to the compound tested.…”
Section: Nomentioning
confidence: 99%